Genetically engineered organisms, wildlife, and habitat : a workshop summary - Whitacre, Paula (National Academies Press, 2008)
This is a summary of a public workshop of experts, resource managers, and others to identify research activities with the greatest potential to provide scientific information and data that would improve the ability to assess the ecological risks and impacts of genetically engineered organisms (GEOs) on terrestrial and aquatic wildlife and their habitats in the United States. The workshop was organized around key concerns related to the interaction of GEOs with natural environments and considered the specific types of data needed to evaluate the risk and impact of GEOs on wildlife and their habitat. In addition to identifying various scientific approaches to obtaining the necessary data, the workshop considered whether and how research needs and approaches for evaluating the risk and impact of GEOs might complement or build on existing research, surveillance, and monitoring activities in natural areas.